Comparison of Physical Profiles of State-Level Netball Players by Position. Issue 9 (September 2020) - Graham, Scott; Duthie, Grant; Aughey, Robert; Zois, James
Abstract : Abstract: Graham, S, Duthie, G, Aughey, R, and Zois, J. Comparison of physical profiles of state-level netball players by position. J Strength Cond Res 34(9): 2654–2662, 2020—Understanding the physical profiles of state-level netball athletes provides conditioning professionals with testing norms and an understanding of important capacities within particular positions. The purpose was to examine positional differences in physical capacities of state-level netball athletes. Forty-six state-level netball athletes completed physical capacity assessments in the second week of their preseason, over 2 seasons. Tests included stature, 20-m sprint (with 5 and 10 m splits), 505 change-of-direction, countermovement jump, single-leg bounding, and the Yo-Yo intermittent recovery test level one. A linear mixed-model with fixed and random effects was used in conjunction with magnitude-based inferences to determine meaningful differences with 90% confidence limits (CLs). Midcourt athletes were shorter in stature than shooters (effect size [ES]: 1.26, CL 0.88–1.63) and defenders (−2.58, −3.35 to −1.80). Midcourt athletes were faster than shooters and defenders in linear acceleration over 5 and 10 m distances and 505 change-of-direction (ES range: −0.34 to −0.59). Shooters presented poorer intermittent endurance than midcourt (−0.82, −1.34 to −0.31) and defenders (−0.56, −1.19 to 0.07). Defenders jumped higher than midcourt athletes (−0.56, −1.30 to 0.19) and shooters (−0.61, −1.18 to −0.04), and possessed greater bounding ability compared with shooters (ES range: −0.23 to −0.57). Midcourt athletes require a more holistic set of physical capacities including acceleration, change-of-direction, jumping, and intermittent endurance. For defender and shooter positions, results indicate physical requirements that may be more specific to their positions. Conditioning professionals can use these findings to target specific physical qualities to maximize position-specific performance.